Variable High-Order Multiblock Overlapping Grid Methods for Mixed Steady and Unsteady Multiscale Viscous Flows, Part II: Hypersonic Nonequilibrium Flows (Communications in Computational Physics, 2018)
The variable high-order multiblock overlapping (overset) grids method ofSjögreen & Yee [CiCP, Vol. 5, 2009] for a perfect gas has been extended to nonequilibrium flows. This work makes use of the recently developed high-order well-balancedshock-capturing schemes and their filter counterparts [Wang et al., J. Comput. Phys.,2009, 2010] that exactly preserve certain non-trivial steady state solutions of the chemical nonequilibrium governing equations. Multiscale turbulence with strong shocksand flows containing both steady and unsteady components is best treated by mixing of numerical methods and switching on the appropriate scheme in the appropriatesubdomains of the flow fields, even under the multiblock grid or adaptive grid refinement framework. While low dissipative sixth- or higher-order shock-capturing filtermethods are appropriate for unsteady turbulence with shocklets, second- and third-order shock-capturing methods are more effective for strong steady or nearly steadyshocks in terms of convergence. It is anticipated that our variable high-order oversetgrid framework capability with its highly modular design will allow for an optimumsynthesis of these new algorithms in such a way that the most appropriate spatial discretizations can be tailored for each particular region of the flow. In this paper some ofthe latest developments in single block high-order filter schemes for chemical nonequilibrium flows are applied to overset grid geometries. The numerical approach is validated on a number of test cases characterized by hypersonic conditions with strongshocks, including the reentry flow surrounding a 3D Apollo-like NASA Crew Exploration Vehicle that might contain mixed steady and unsteady components, dependingon the flow conditions.